Enteral feeding of premature infants with Lactobacillus GG. Issue 5 (November 1993) - Millar, M R; Bacon, C; Smith, S L; Walker, V; Hall, M A
Abstract : The objectives of this study were to determine whether or not the probiotic Lactobacillus GG can colonise the immature bowel of premature infants and if so, does colonisation result in a reduction of the size of the bowel reservoir of nosocomial pathogens such as enterobacteriaceae, enterococci, yeasts or staphylococci, and does colonisation with Lactobacillus GG have any effect on the clinical progress and outcome. Twenty preterm infants with a gestational age of 33 weeks or less who were resident on a neonatal unit were studied from the initiation of milk feeds until discharge. The infants were randomised to receive either milk feeds or milk feeds supplemented with Lactobacillus GG 10(8) colony forming units twice a day for two weeks. The clinical features of the two groups of infants were similar. Orally administered Lactobacillus GG was well tolerated and did colonise the bowel of premature infants. However, colonisation with Lactobacillus GG did not reduce the faecal reservoir of potential pathogens and there was no evidence that colonisation had any positive clinical benefit for this particular group of infants.